Wicked bite - Frost, Jeaniene (Frost, Jeaniene. Night rebel novel., 2020)
Veritas spent most of her life as a vampire Law Guardian. Now, she's about to break every rule by secretly hunting down the dark souls that were freed in order to save Ian. But the risks are high. For if she gets caught, she could lose her job. And catching the sinister creatures might cost Veritas her own life.